LA OBSERVACIÓN CASUAL DE LAS TRANSFORMACIONES SOCIO-MEDIÁTICAS DESDE LA MIRADA DE LA CÁMARA: PRIMEROS INDICIOS EN MONTREAL Y MÉXICO DF EN LOS AÑOS NOVENTA / CASUAL OBSERVATION OF SOCIO-MEDIATIC TRANSFORMATIONS FROM DE CAMERA PERSPECTIVE: FIRST EVIDECENCES IN MONTREAL AND MEXICO D.F. IN THE 1990s - García, Nicolás Lorite (Vivência: Revista de Antropologia, 2017)
Este artigo descreve as primeiras evidências de um método próprio de pesquisa audiovisual (aplicada) obtidas a partir de observação casual (mas não rasa) mediatizada por câmera no Grupo de Pesquisa sobre Indústrias Culturais e Informatização Social da Universidade de Quebec, Canadá, e no Instituto Tecnológico e de Estudos Superiores de Monterrey, México, em 1999. ABSTRACT In this paper I describe the first evidences of an own (applied) audio-visual research method obtained after a camera mediatised casual (though not shallow) observation in the GRICIS-UQAM (Montreal) during 1996 and 1997 and in the TEC Monterrey (Mexico DF) in 1999.